Sorafenib in combination with docetaxel as first-line therapy for HER2-negative metastatic breast cancer: final results of the randomized, double-blind, placebo-controlled phase II MADONNA study - Mavratzas, Athanasios; Baek, Sunhwa; Schneeweiss, Andreas; Marmé, Frederik (The breast, 2019)
Abstract Background. This multicenter, double-blind phase II study assessed the antitumor activity and toxicity profile of docetaxel with the antiangiogenic multikinase inhibitor sorafenib or matching placebo as a first-line treatment in patients with metastatic or locally advanced HER2-negative breast cancer. Patients and methods: Patients were randomized 1:1 to receive docetaxel 100mg/m2 on day 1 every 3 weeks in combination with sorafenib 400mg bid or placebo on days 2–18 of each cycle until tumor progression, or unacceptable toxicity. Sorafenib/placebo could be continued at the investigator's discretion if docetaxel was stopped due to toxicity. Primary endpoint was progression free survival (PFS). Results: From October 2008 to December 2013, 102 patients were randomized; 98 patients were evaluable. The trial was prematurely terminated due to slow accrual. Due to increased toxicity the dose of docetaxel was reduced to 75mg/m2 and an increasing sorafenib dosing schedule was implemented as part of a protocol amendment. The addition of sorafenib to docetaxel did not improve PFS (8.2 vs. 7.3 months for docetaxel/placebo; HR 0.84, log rank p=0.43), but led to higher rates of early treatment discontinuation. There were no statistically significant differences between sorafenib dosing schedules. Conclusions: Addition of sorafenib to taxane-based first-line chemotherapy in patients with metastatic breast cancer failed to improve PFS and resulted in increased toxicity.
Gesehen am 12.08.2019